2009
DOI: 10.1042/bj20081677
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective effects of IAPs revealed by a small molecule antagonist

Abstract: SYNOPSIS Deregulated expression of members of the Inhibitor of Apoptosis (IAP) family has been found in a wide variety of neoplastic cells, and synthetic IAP antagonists represent a promising novel class of chemotherapeutic agents. Early work focused on the ability of these compounds to block the caspase inhibitory function of XIAP. However, recent studies have shown that IAP antagonists, although primarily designed to target XIAP, trigger a ubiquitin-mediated degradation of two related proteins, c-IAP1 and c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…Accordingly, there is increasing experimental evidence that small molecule IAP antagonists can sensitise resistant cancer cells towards TRAIL and/or TNF-induced killing, either given as single agents, or in combination with classical chemotherapeutic drugs (Figure 3). [112][113][114][115][116] The IAP antagonists available today target multiple members of the IAP family, including cIAP1, cIAP2 and XIAP (see Table 1 for an overview of current clinical trials using IAP antagonists). 117 Given the role of cIAP1 and cIAP2 in the regulation of proximal events in TNF-R1 signalling, 117,118 antagonists that are highly specific for XIAP may be even better suited than broad spectrum IAP inhibitors for cancer therapy.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Accordingly, there is increasing experimental evidence that small molecule IAP antagonists can sensitise resistant cancer cells towards TRAIL and/or TNF-induced killing, either given as single agents, or in combination with classical chemotherapeutic drugs (Figure 3). [112][113][114][115][116] The IAP antagonists available today target multiple members of the IAP family, including cIAP1, cIAP2 and XIAP (see Table 1 for an overview of current clinical trials using IAP antagonists). 117 Given the role of cIAP1 and cIAP2 in the regulation of proximal events in TNF-R1 signalling, 117,118 antagonists that are highly specific for XIAP may be even better suited than broad spectrum IAP inhibitors for cancer therapy.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Recent study has indicated that IAP inhibitors can target multiple IAPs (that is, XIAP, c-IAP) to enhance the activity of different proapoptotic signaling pathways (Galban et al, 2009). However, the role of XIAP in intrinsic versus extrinsic death pathways is unclear; recent studies suggest that it has a more significant role in regulating death receptor-mediated apoptosis than intrinsic pathway-mediated cell death (Sensintaffar et al, 2010).…”
Section: Targeting Bone Marrow Microenvironmentmentioning
confidence: 99%
“…10 This result suggests that XIAP is required to protect nascent c-IAP2 from degradation. To confirm this hypothesis, XIAP-null HCT116 18 and MEF cells 19 were treated with TNFα, and then c-IAP2 levels were measured. The 2 h TNF=induced upregulation of c-IAP2 was attenuated in XIAP-null HCT116 cells (Fig.…”
Section: Xiap Upregulates C-iap2 In Gbm Cell Linesmentioning
confidence: 99%
“…MEF cells with wild-type or knocked-out XIAP were transformed with v-Ras/v-E1A, and HCT116 cells with wild-type or null XIAP were cultured as described previously. 18,19 TNFα (8902) was purchased from Cell Signaling.…”
Section: Cells and Reagentsmentioning
confidence: 99%